Survey on Simulators for Underwater Sensor Networks - et. al., Geeta Godi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The deployment of the Underwater Sensor Network (UWSN) is extremely complex due to water characteristics. The real-time implementation of UWSN applications needs to analyze the practical consideration. To prevail these difficulties, UWSN simulation tools play a significant role especially in studying the underwater environment and also to test the new algorithms, applications, and protocols. In this paper, we explore various underwater simulators and classified them based on the programming languages. Further, we discuss on credibility and challenges posed by the simulators. This work encourages the researcher to choose an appropriate simulation tool for the UWSN application.